Mitochondrial DNA Inheritance in the Human Fungal Pathogen Cryptococcus gattii - WANG, ZIXUAN (My University, 2014)
The inheritance of mitochondrial DNA (mtDNA) is predominantly uniparental in most sexual eukaryotes, including the human pathogenic basidiomycetous yeast Cryptococcus neoformans. In this study, we examined the mitochondrial inheritance pattern of Cryptococcus gattii, a closely - related sister species of C. neoformans responsible for the recent and ongoing outbreak of Cryptococcal infections in the US Pacific Northwest and British Columbia (especially Vancouver Island) in Canada. Using molecular markers, we analyzed the inheritance of mitochondrial DNA in 9 crosses between strains within and between divergent lineages in C. gattii. Our analyses identified significant variations in mtDNA inheritance patterns among strains and crosses. For two of the crosses that showed uniparental mitochondrial inheritance in standard laboratory conditions, we further investigated the effects of the following environmental variables on mtDNA inheritance: UV exposure, temperature, exposure to the methylation inhibitor 5-aza-2’-deoxycytidine, and exposure to the ubiquitination inhibitor ammonium chloride. Interestingly, one of these crosses showed no response to these environmental variables while the other exhibited diverse patterns ranging from complete uniparental inheritance of the MATa parent mitochondria, to biparental inheritance, and to complete uniparental inheritance of the MATalpha parental mitochondria. Our analyses indicated that the mtDNA inheritance pattern in C. gattii differs significantly from its closely related species C. neoformans. We discussed possible mechanisms underlying these divergent mitochondrial DNA inheritance pattern.
Masters Thesis
Keywords: Masters Thesis